2018
DOI: 10.1002/humu.23428
|View full text |Cite|
|
Sign up to set email alerts
|

Mutation update for theGPC3gene involved in Simpson-Golabi-Behmel syndrome and review of the literature

Abstract: Simpson-Golabi-Behmel syndrome (SGBS) is an X-linked multiple congenital anomalies and overgrowth syndrome caused by a defect in the glypican-3 gene (GPC3). Until now, GPC3 mutations have been reported in isolated cases or small series and the global genotypic spectrum of these mutations has never been delineated. In this study, we review the 57 previously described GPC3 mutations and significantly expand this mutational spectrum with the description of 29 novel mutations. Compiling our data and those of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 67 publications
(110 reference statements)
0
17
0
Order By: Relevance
“…[3,4] Diagnosis of SGBS1 in males is established by observable clinical manifestations and/or detection of a pathogenic variant of GPC3, or a large duplication of GPC3 and/or GPC4. [5,6] In the present report, we describe a neonate of SGBS1 with a nonsense mutation in GPC3 presenting hypothyroidism and subclinical hypothyroidism.…”
Section: Introductionmentioning
confidence: 85%
“…[3,4] Diagnosis of SGBS1 in males is established by observable clinical manifestations and/or detection of a pathogenic variant of GPC3, or a large duplication of GPC3 and/or GPC4. [5,6] In the present report, we describe a neonate of SGBS1 with a nonsense mutation in GPC3 presenting hypothyroidism and subclinical hypothyroidism.…”
Section: Introductionmentioning
confidence: 85%
“…Children with BWS are also at risk of developing hepatoblastoma ( 24). An x-linked overgrowth syndrome associated with the GPC3 gene, patients with SGBS exhibit macrosomia, macrocephaly, organomegaly, distinct facial features, and abnormalities across most organ systems, including genitourinary anomalies (25). Newborns may experience hypoglycemia or have airway issues secondary to micrognathia and glossoptosis.…”
Section: Moderate Risk Syndromesmentioning
confidence: 99%
“…Up to now, GPC3 remains the only gene surely involved in SGBS. To date, 86 distinct GPC3 variants have been reported in 120-unrelated patients [6]. These variants, mostly inherited, are dispersed throughout the whole-coding region of the gene with no obvious variant hotspots.…”
Section: Mutational Spectrummentioning
confidence: 99%
“…SGBS is very rare and its exact prevalence is unknown. In a recent review of the literature we have identified 152 male patients, belonging to 120-unrelated families, with a GPC3 variant [6]. In their review, Tenorio et al [7] mentioned that 250 patients had been reported in the literature, but they included patients for whom misdiagnosis was possible as no confirmation by a molecular analysis was performed.…”
Section: Analytical Validationmentioning
confidence: 99%